Nurse Integrity Through Professional Organization Development in Tulungagung Regency: Integritas Perawat Melalui Pengembangan Organisasi Profesi di Kabupaten Tulungagung - Karingga, Devangga Darma; Prasetyawan, Fendy; Purnomo; Fitriani, Evi Tunjung (Journal of Social and Community Service, 2024)
Integrity in the nursing profession includes honesty, fairness, responsibility, and commitment to professional ethics. This research aims to improve the integrity of nurses through a community service program that involves collaboration with the Indonesian National Nurses Association (PPNI). This program consists of ethics training and education, drafting and updating a code of ethics, and developing policies that support integrity in nursing practice. The methods used include initial surveys, focus group discussions (FGD), Training of Trainers (ToT) programs, as well as mentoring and counseling. Results showed significant improvements in nurses' understanding and skills regarding integrity, as well as increased institutional support. Post- training evaluations and follow-up surveys showed that most participants reported improvements in implementing integrity principles in daily practice. However, challenges such as high workloads remain and require further attention. This program proves that with the right approach and commitment from all parties involved, improving nurse integrity can be achieved, which will ultimately provide great benefits for patients and the health system.